Covid‐19 and the digestive system - Wong, Sunny H; Lui, Rashid NS; Sung, Joseph JY (Journal of gastroenterology and hepatology, 2020)
The novel coronavirus disease is currently causing a major pandemic. It is caused by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), a member of the Betacoronavirus genus that also includes the SARS‐CoV and Middle East respiratory syndrome coronavirus. While patients typically present with fever and a respiratory illness, some patients also report gastrointestinal symptoms such as diarrhea, vomiting, and abdominal pain. Studies have identified the SARS‐CoV‐2 RNA in stool specimens of infected patients, and its viral receptor angiotensin converting enzyme 2 was found to be highly expressed in gastrointestinal epithelial cells. These suggest that SARS‐CoV‐2 can actively infect and replicate in the gastrointestinal tract. This has important implications to the disease management, transmission, and infection control. In this article, we review the important gastrointestinal aspects of the disease.